An implementation of fuzzy logic controller on the reconfigurable FPGA system - Kim, Daijin (IEEE transactions on industrial electronics (1982), 2000)
This paper concerns an implementation of a fuzzy logic controller (FLC) on a reconfigurable field-programmable gate array (FPGA) system. In the proposed implementation method, the FLC is partitioned into many temporally independent functional modules, and each module is implemented individually on the FLC automatic design and implementation system, which is an integrated development environment for performing many subtasks such as automatic VHSIC hardware description language description, FPGA synthesis, optimization, placement and routing, and downloading. Each implemented module forms a downloadable hardware object that is ready to configure the FPGA chip. Then, the FPGA chip is consequently reconfigured with one module at a time by using the run-time reconfiguration method. This implementation method is effective when a single FPGA chip cannot fit the FLC due to the limited size of its constituent cells. We test the proposed implementation method by building the FLC for the truck backer-upper control on VCC Corporation's EVC-1 reconfigurable FPGA board directly.